Kedudukan Amicus Curiae Dalam Sistem Peradilan Di Indonesia - Linda Ayu Pralampita (Lex Renaissance, 2020)
This article discusses the position of Amicus Curiae's opinion in the Indonesian judicial system. The method used is normative legal research using a statutory approach. The results of this study conclude that Amicus Curiae is not widely known but has been practiced in the judicial system in Indonesia. Thus, Amicus Curiae is one of the elements in the judicial system in Indonesia that does not yet have a standardized form, because there is no clear and specific regulation regarding this matter. In the judicial system in Indonesia, Amicus Curiae's position cannot be considered as a witness statement or an expert witness, because Amicus Curiae is more of a public participation whose opinion is accepted and can be considered by the judges.